2021
DOI: 10.1093/bjs/znab330
|View full text |Cite
|
Sign up to set email alerts
|

GORD and Barrett’s oesophagus after bariatric procedures: multicentre prospective study

Abstract: Introduction Gastro-oesophageal reflux disease (GORD) after bariatric surgery is a debated topic. This study investigated the prevalence of GORD and associated oesophageal complications following bariatric procedures—namely, adjustable gastric banding (AGB), sleeve gastrectomy (SG), Roux-en-Y gastric bypass (RYGB), and one-anastomosis gastric bypass (OAGB). Methods This was a prospective multicentre study designed to evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 36 publications
1
13
0
1
Order By: Relevance
“…Again, concordant to the current literature evidence for LINX® magnetic sphincter device is low, since only a few cohort studies exist [32][33][34]. Cruroplasty/hiatal hernia repair might not be taken into consideration, since SG remains a high-pressure system and GERD seems to improve only after RYGB [35].…”
Section: Symptomatic Gerd After Sg and Excessive Weight Losssupporting
confidence: 56%
“…Again, concordant to the current literature evidence for LINX® magnetic sphincter device is low, since only a few cohort studies exist [32][33][34]. Cruroplasty/hiatal hernia repair might not be taken into consideration, since SG remains a high-pressure system and GERD seems to improve only after RYGB [35].…”
Section: Symptomatic Gerd After Sg and Excessive Weight Losssupporting
confidence: 56%
“…This is in striking contrast with data from South America, where RYGB remains central and accounts for around 60% of BS activity and with Asia where RYGB was historically around 10% and remained so [ 13 , 14 ]. RYGB remains considered by many the gold standard BS technique, due to its long-standing efficacy and safety and its superiority in the treatment of GERD [ 19 ]. However, RYGB is technically complex and long-term data have evidenced its fallibility [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…This was unprecedented in previous studies. This trend is probably the result of tapering off of the initial enthusiasm, as time has made clear that SG has its own limitations including sub-optimal long-term efficacy and difficult-to-manage complications such as gastric leak and chronic GERD [15][16][17][18][19]. In fact, the absolute reduction in main non-malabsorptive procedures although small (6% between 2011 and 2021) was indeed significant.…”
Section: Discussionmentioning
confidence: 99%
“…They found that RYGB was superior to OAGB and SG, not only in terms of GERD symptoms but also when monitoring Gastritis, Barrett´s esophagus, anastomotic inflammation, and biliary reflux to the stomach and esophagus. Only in terms of marginal ulcers, OAGB and RYGB were not significantly different [ 28 ]. On the other hand, the latest update (10 years of follow-up) of the SLEEVEPASS trial by Salminen et al showed that both in SG and RYGB Barrett´s esophagus rates were low (4%), even with much higher symptomatic de-novo reflux rates.…”
Section: Discussionmentioning
confidence: 99%